Modeling the effectiveness of Esperanza window traps as a complementary vector control strategy for achieving the community-wide elimination of onchocerciasis - Shakir Bilal; Morgan E. Smith; Swarnali Sharma; Wajdi Zaatour; Ken Newcomb; Thomas R. Unnasch; Edwin Michael (Frontiers in Tropical Diseases)
IntroductionMathematical models of parasite transmission are essential tools for evaluating the impact of interventions aimed at controlling or eliminating community-level disease transmission. These models integrate field observations with transmission dynamics to optimize intervention strategies. In this study, we assess the effectiveness of the Esperanza Window Trap (EWT), a novel black fly control tool, as a complementary strategy to mass drug administration (MDA) for eliminating Onchocerca volvulus transmission in endemic settings.MethodsWe coupled seasonally-driven onchocerciasis transmission models, calibrated for representative villages in Uganda, with a spatially-informed landscape model simulating various EWT trap configurations. This integrated framework allowed us to evaluate the impact of EWT deployment on Simuliid fly populations and onchocerciasis transmission dynamics under different scenarios, including concurrent use with MDA and post-MDA deployment.ResultsOur simulations show that combining EWT traps with MDA programs significantly reduces the time required to achieve elimination targets compared to MDA alone. Furthermore, deploying EWT traps after cessation of MDA enhances the long-term sustainability of onchocerciasis elimination. The number of traps needed depends on factors such as trap efficiency, capture range, inter-trap distance, site size, and spatial heterogeneity of fly populations.DiscussionThese findings demonstrate the feasibility and effectiveness of EWT as a supplementary intervention to accelerate and sustain community-wide onchocerciasis elimination. The integration of landscape-level EWT deployment with seasonal transmission models also illustrates how macroparasite models can be extended to incorporate spatio-temporal processes, offering valuable insights for optimizing vector control strategies.